Multiplex PCR for the detection of Salmonella spp. in Indonesian traditional shrimp paste (Terasi) - Affan Gaffar; Yoga Dwi Jatmiko; Asep Awaludin Prihanto (The East Java Biological Society, 2022)
Terasi is a food condiment originating from Indonesia which is processed by fermenting shrimp, fish, or a mixture of both. The processing of terasi in Indonesia is still found traditionally so that it will affect the low quality of terasi which is characterized by being contaminated by pathogenic bacteria such as Salmonella. Salmonella is a bacterium that causes foodborne diseases. The purpose of this study was to evaluate the presence of Salmonella in shrimp paste using conventional method and then confirmed with molecular approach. This study used 10 samples consisting modern terasi and five traditional terasi. The isolation of Salmonella spp. carried out by using selective media, and then the isolates were characterized further using biochemical test (TSIA and LIA). The species identification of Salmonella spp. was carried out by multiplex PCR (mPCR). The isolates that were not detected by mPCR were further identified using 16s rDNA sequencing. The isolation results showed that Salmonella isolates were only detected in traditional terasi with a density range of 2.4 x 1052.9 x 108 CFU/g. A total of 20 isolates were characterized biochemically as Salmonella, and out of 17 isolates consistently identified as Salmonella enterica serovar Typhimurium by using mPCR. The rest three isolates were further identified as Citrobacter freundii based on 16s rDNA sequencing with similarity level of 99%. The presence of Salmonella in the shrimp paste indicates that the processing of traditional shrimp paste (terasi) should be evaluated in accordance with good manufacturing process.